A scoping review protocol of existing body image guidelines for parents of youth - Madison F. Vani; Alishba Mansoor; Elise Christopoulos; Fengyue Xu; Landyn Meadows; Catherine M. Sabiston (PLoS ONE, 2026)
Body image concerns are commonly experienced by youth in sport and contribute to worse sport experiences and dropout. Parents are positioned to ensure the sport environment is safe and positive for their child, but they do not feel equipped to help their children with body image concerns. Providing parents with tools to support their children is needed. To develop parent-focused body image in sport guidelines, it is necessary to comprehensively summarize parent resources for fostering an adaptive body image among youth. This scoping review will synthesize the available guidelines and/or recommendations for parents on youth body image. The objectives are to (1) identify how many guidelines/recommendations exist for parents to support youth body image; (2) illustrate the guidelines/recommendations’ characteristics (i.e., resource type/format; method(s) used to develop resource); and (3) describe the topics/content covered in the guidelines/recommendations. An eight-step methodological framework including parent consultations will inform the review process. The protocol has been registered ( https://osf.io/9hq78 ). Nine databases (Embase, PsycINFO, Social Work Abstracts, and MEDLINE via Ovid, CINAHL, Gender Studies, and SportDiscus via EBSCO, and ERIC and Sociological Abstracts via ProQuest) were searched from January 1, 2014 to February 11, 2025. Inclusion criteria are: qualitative, quantitative, mixed methods, and review articles; written in English; and include recommendations or guidelines developed for parents of children aged 4–18 years and focused on at least one aspect of body image. Titles, abstracts, and full-text articles were screened in duplicate using eligibility criteria. Extracted data will be analyzed using a descriptive numerical summary and conventional content analysis. Institutional research ethics board approval was obtained for parent consultations. The consultations will be integrated with the results and disseminated through academic conferences and a peer-reviewed publication. Findings will also inform the development of parent-focused guidelines for youth body image in sport.